2017
DOI: 10.1016/j.oregeorev.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and lead isotopic compositions of massive sulfides from deep-sea hydrothermal systems: Implications for ore genesis and fluid circulation

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 114 publications
5
16
0
2
Order By: Relevance
“…The S sources in sediment-starved fields were mainly seawater-derived sulfate and magmatic sulfur [25]. Based on two-component mixing model (δ 34 S -mix = X × δ 34 S seawater + (1 − X) × δ 34 S basalt [25][26][27]). The δ 34 S seawater , δ 34 S basalt , and δ 34 S -mix represent 21 , 0 and the isotope values of the Wocan-1 and Wocan-2 samples, while, the unknown value (X) represents the amount of seawater component.…”
Section: The Contributions Of Hydrothermal Fluid Evidence From S Isomentioning
confidence: 99%
“…The S sources in sediment-starved fields were mainly seawater-derived sulfate and magmatic sulfur [25]. Based on two-component mixing model (δ 34 S -mix = X × δ 34 S seawater + (1 − X) × δ 34 S basalt [25][26][27]). The δ 34 S seawater , δ 34 S basalt , and δ 34 S -mix represent 21 , 0 and the isotope values of the Wocan-1 and Wocan-2 samples, while, the unknown value (X) represents the amount of seawater component.…”
Section: The Contributions Of Hydrothermal Fluid Evidence From S Isomentioning
confidence: 99%
“…Compared to sulfides from mid‐oceanic ridges, sulfides from the OT are notably enriched in Zn and Pb (Glasby & Notsu, ; Ishibashi, Ikegami, Tsuji, & Urabe, ). Studies on the rare earth elements (REEs), sulfur‐lead‐osmium‐zinc and noble gas isotopes, and the compositional characteristics of fluid inclusions of massive sulfides have shown that the endmembers of seawater, felsic volcanic rocks, and marine sediments may be the sources that formed the massive sulfides in the hydrothermal field of the OT (Halbach, Hansmann, Köppel, & Pracejus, ; Hongo & Nozaki, ; Hou, Zhang, & Qu, ; Lüders, Pracejus, & Halbach, ; Zeng et al, ; Zeng, Jiang, Qin, Zhai, & Hou, ; Zeng, Jiang, Zhai, & Qin, ; Zeng, Qin, & Zhai, ; Zeng, Zhai, & Du, ; Zhang, Zhai, Yu, Guo, & Wang, ). The Pb isotope compositions of galena in hydrothermal deposits in the middle OT also reflect that their metal sources originated from either the local volcanic rocks and/or the sediments via water–rock interactions (Totsuka et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…It was suggested that the combination of the troctolite-alteration at the recharge zone near the oceanic core complex and subsequent basalt-alteration at the discharge zone under the Kairei is causing the distinct chemistry of the hydrothermal fluids [18,25]. Recent investigations have shown the presence of other hydrothermal deposits (Yokoniwa, and 25°09′S) in the area [26,28]. were optimized in order to provide a maximum in ion transmission, a low polyatomic cluster production rate (ThO/Th ≤ 0.03%; CuAr/Cu < 0.0025%) by hot plasma (normalized argon index NAI≈30; [33]) and a fast sample wash-out.…”
Section: Geological Backgroundmentioning
confidence: 99%